These spots of excavation tell: using early visitor accounts to map the missing graves of waterloo. Issue 2 (4th May 2021) - Pollard, Tony
ABSTRACT: This paper uses the writings of early visitors to the field of Waterloo to examine the treatment of the dead following the battle fought on 18 June 1815. It is proposed that these memoirs and journals, along with various artworks, contain information that can assist not only in the explanation of the complexities of body disposal, but also guide us to the location of grave sites on the battlefield. It is further suggested, on the basis of the picture building from recent archaeological investigations, that at least some of the larger graves were exploited for human and animal bone, which in the first half of the nineteenth century served as an important source of phosphate fertilizer.